The Impact of Past Trauma on Psychological Distress: The Roles of Defense Mechanisms and Alexithymia - Fang, Siqi; Chung, Man Cheung; Wang, Yabing (Frontiers in Psychology, 2020)
Objectives: Posttraumatic stress disorder symptoms (PTSD) following past trauma could lead to psychological distress. Little is known, however, about the roles of defense mechanisms and alexithymia may play in the process. The current study aimed to examine the potential impact of alexithymia and defense mechanisms on the relationship between past trauma and distress among Chinese university students. Method: 455 university students completed a set of questionnaires: PTSD Checklists for DSM-5, Toronto Alexithymia Scale, Defense Style Questionnaire, and General Health Questionnaire-28. Results: PTSD following past trauma was associated with increased psychological distress. Alexithymia and defenses (especially immature defense) mediated the path between PTSD and psychological co-morbidities. Conclusions: Following past trauma, people developed PTSD and other psychological symptoms. The severity of these distress symptoms was influenced by the way people defended themselves psychologically, as well as their ability to identify, express, and process distressing emotions.